Light and optics : principles and practices - Al-Azzawi, Abdul (CRC Press, 2007)
THE NATURE OF LIGHTIntroductionThe Evolution of Light TheoryMeasurements of the Speed of LightLight SourcesThe Electromagnetic SpectrumTypes of Electromagnetic WavesProperties of LightFurther ReadingLIGHT AND SHADOWSIntroductionShadowsSolar EclipseLunar EclipseApplications of ShadowsExperimental WorkList of ReferencesAppendicesFurther ReadingTHERMAL RADIATIONIntroductionThermal RadiationLight and EnergySolar Radiation EnergyClassification of Solar CollectorsFlat-Plate CollectorsSolar Heating SystemsHot Water and Steam Generation SystemsVapour Absorption Refrigeration/Air Conditioning SystemsPh.